Aquinas’s Miracles and the Luciferous Defence: The Problem of the Evil/Miracle Ratio - Luck, Morgan (Sophia, 2009)
Miracles and the problem of evil are two prominent areas of research within philosophy of religion. On occasion these areas converge, with God’s goodness being brought into question by the claim that either there is a lack of miracles, or there are immoral miracles. In this paper I shall highlight a second manner in which miracles and the problem of evil relate. Namely, I shall give reason as to why what is considered to be miraculous may be dependent upon a particular response to the problem of natural evil. To establish this claim, I shall focus upon Aquinas’s definition of a miracle and a particular free-will defence, the Luciferous defence.